'Escaping' managed labour migration: worker exit as precarious migrant agency. Issue 4 (3rd July 2020) - Perry, J. Adam
ABSTRACT: This article narrows in on the mundane yet extraordinary events surrounding migrant farm workers' decisions to leave their state-approved employment and to seek a better life in Canada outside of state-managed circulatory labour migration. In so doing, this research contributes to conceptualisations of precarity, and of precarious status in particular, that are beginning to recognise its effects not only on workers' economic survival, but also the more ordinary daily conditions surrounding workers' sense belonging and personal autonomy. In their refusal to accept the terms of their contractual circulatory labour migration agreements through what is conceptualised here as an act of 'escape', workers claim a space of belonging that contradicts the precarity of their formal citizenship status. In carving out a space in which they may perform autonomy and self-determination in daily life, however, this rejection of contingent citizenship status intensifies the precarious material conditions governing workers' relationship to the state.